2013
DOI: 10.1016/j.psychres.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The importance of self-determined motivation towards physical activity in patients with schizophrenia

Abstract: There is a need for theoretically-based research on the motivational processes linked to the commencement and continuation of physical activity in patients with schizophrenia. Within the Self-Determination Theory (SDT) framework, we investigated the SDT tenets in these patients by examining the factor structure of the Behavioral Regulation in Exercise Questionnaire-2 (BREQ-2) and by investigating associations between motivation and PA. The secondary aim was to study differences in motivation according to gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 32 publications
9
95
0
Order By: Relevance
“…The questionnaire comprised 19 items relating to five motivation types from the SDT. In accordance with previous research 23 in people with schizophrenia "identified regulation" and "intrinsic regulation" were combined to a single factor labelled "autonomous regulation". Each item is measured on a five-point Likert-scale, from 0 ('Not true for me') to 4 ('Very true to me').…”
Section: Accepted M Manuscriptmentioning
confidence: 64%
“…The questionnaire comprised 19 items relating to five motivation types from the SDT. In accordance with previous research 23 in people with schizophrenia "identified regulation" and "intrinsic regulation" were combined to a single factor labelled "autonomous regulation". Each item is measured on a five-point Likert-scale, from 0 ('Not true for me') to 4 ('Very true to me').…”
Section: Accepted M Manuscriptmentioning
confidence: 64%
“…The current study demonstrates that with an appropriately standardised method, the AstrandRhyming test is highly reproducible in patients with schizophrenia or schizoaffective disorder facing motivation problems when performing physical activities (Vancampfort et al, 2013b).…”
Section: Feasibilitymentioning
confidence: 71%
“…However, these test protocols are time-consuming, costly and need highly sophisticated equipment (Vanhees et al, 2005), which is often not available or practical in mental health care settings. Moreover, the maximal nature of the test may be influenced by the motivation of participants (Strassnig et al, 2011;Vancampfort et al, 2013b). Submaximal exercise tests that use measures of heart rate (HR) to estimate V0 2 max are considered to be a reliable and valid measure of aerobic fitness (Lambrick, Faulkner, Rowlands, Eston, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…If time permits, the psychiatrist could briefly explore the patient's readiness for change as it relates to their physical activity , and use evidence-based behavior change principles to guide patients toward a more physically active lifestyle (Vancampfort et al, 2013b). When time does not permit, or when patients are confronted with severe depressive or manic symptoms and are consequently struggling to be more physically active (Vancampfort et al, 2013a) and/or those who are suffering from cardiovascular, respiratory, neurological or musculoskeletal conditions, may also benefit from further evaluation by a physical therapist or exercise physiologist .…”
Section: Practical Implicationsmentioning
confidence: 99%